2003
DOI: 10.1055/s-2003-41197
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance, SPECT, and Blood Viscosity in Elderly Non-demented People Using Ginkgo Biloba

Abstract: The aging process is associated with several cognitive alterations. This study looks at the effects of taking dried extract of Ginkgo biloba, which has been used in several countries in an attempt to minimize these effects. The subjects were 48 men aged 60 - 70 matched between control and experimental groups for educational level. Evaluation was based on a number of neuropsychological tests in an attempt to cover the largest possible number of functions including Single Photon Emission Computer Tomography (SPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…The current results did not duplicate the findings of the previous SPECT study [12], which reported significantly increased CBF in many various brain regions including the left frontal, frontoparietal, and parietal and right frontal and parietal lobes. This could be due to a number of methodological differences, including the dose and duration of EGb administration, lobar segmentation and ROI selections, subject inclusion criteria, and imaging methods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current results did not duplicate the findings of the previous SPECT study [12], which reported significantly increased CBF in many various brain regions including the left frontal, frontoparietal, and parietal and right frontal and parietal lobes. This could be due to a number of methodological differences, including the dose and duration of EGb administration, lobar segmentation and ROI selections, subject inclusion criteria, and imaging methods.…”
Section: Discussioncontrasting
confidence: 99%
“…One multicenter study found that EGb treatment significantly improved cognitive deficits in mildly to severely demented subjects with Alzheimer’s disease (AD) or multi-infarct dementia [11]. Another study showed a significant increase in CBF [using single-photon emission computed tomography (SPECT)], decrease in blood viscosity, and cognitive improvement after chronic EGb use in elder volunteers, suggesting a beneficial effect for demented patients [12]. However, results from the recently completed Ginkgo Evaluation of Memory (GEM) trial [1], a multicenter randomized controlled trial with 3069 participants older than 75 years, demonstrated that EGb did not lower the incidence of dementia or AD in elderly people with normal cognition or minimal cognition deficits.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the present study, four physiological effects described for EGb 761 seem to be most important for the prophylactic effects on NIHL and tinnitus development reported here. These are, first, stabilization of mitochondrial respiratory chain metabolism and ATP production due to antioxidant effects that reduce oxidative stress by elimination of ROS [17, 18]; second, increase of extracellular dopamine levels in prefrontal cortex that may improve mood and thereby reduce stress [26], based on blocking dopamine reuptake via the norepinephrine transporter [28]; third, reduction of hormonal stress responses by reduction of corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), or corticosterone [46]; and fourth, improved blood flow [47, 48]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition to electrophysiological studies of the effects of GBE on the brain, Santos and colleagues [45] utilized single photon emission computed tomography (SPECT) to examine the neurophysiological effects of 8 months of 80 mg/day GBE supplementation versus placebo in elderly healthy males. Santos and colleagues [45] reported that the group receiving GBE displayed increased cerebral perfusion in several areas including bilateral frontal, bilateral parietal, right-frontal parietal, left temporal, and right occipital brain regions. Similar improvements to cerebral perfusion have also been reported following GBE treatment for brain circulation insufficiency [46].…”
Section: Introductionmentioning
confidence: 99%